Reorganizing split objects - Astudillo R., Hernán; Shilling, John J. (1996)
Object-based (i.e. classless) models are very effective for elucidating requirements from users, and they support exploratory programming and rapid prototyping, providing a direct manipulation approach. On the other hand, class-based models have powerful mechanisms to control redundancy, exploit sharing, express extension, and propagate changes to instances.The price object-based approaches pay is loss of control over change propagation, and potential redundancy. Two mechanisms to overcome this are sharing among objects and definition of objects as extension of others. We examine these mechanisms, and consider the effect that interacting policies for objects sharing and definition-by-extension have on change propagation and replication control. An implication is that, in absence of meta-objects or extra-language support, monolithic shared parts cannot coexist with prototypes represented as split objects.
Formato de archivo: PDF. -- Disponible también en línea (Cons. 20/04/2009)
ACM SIGPLAN Notices 1996 31(10) : 138 - 149 .
Keywords: PROGRAMACIÓN ORIENTADA A OBJETOS; SMALLTALK; C++